Indicators of Burnout and Recovery in Early-Career Psychologists: A Thematic Analysis - Saadati, Seyed Milad; Khadem Fini, Armin (Journal of Assessment and Research in Applied Counseling (JARAC), 2026)
Objective: The objective of this study was to explore the indicators of burnout and the strategies of recovery among early-career psychologists, with a focus on their lived experiences within the Irish professional context.Methods and Materials: This qualitative study employed a thematic analysis design. Twenty early-career psychologists practicing in Ireland participated in semi-structured interviews, selected through purposive sampling. Participants represented diverse professional settings including public health services, private practice, community organizations, and academic contexts. Data collection continued until theoretical saturation was achieved. Interviews were audio-recorded, transcribed verbatim, and analyzed using Braun and Clarke’s six-phase framework, supported by NVivo 14 software for data management and coding.Findings: Analysis revealed four overarching themes: (1) Indicators of Burnout, including emotional exhaustion, cognitive strain, physical symptoms, behavioral withdrawal, loss of motivation, and cynicism; (2) Work-Related Stressors, such as excessive caseloads, limited autonomy, organizational climate challenges, career insecurity, peer competition, and inadequate supervision; (3) Coping and Recovery Strategies, encompassing self-care practices, professional and social support, boundary setting, skill development, and meaning-making processes; and (4) Facilitators of Resilience and Growth, including personal traits, supportive work environments, professional identity, work-life integration, positive client outcomes, and continuous development. Illustrative participant quotations highlighted the interplay between strain and recovery, underscoring both vulnerabilities and strengths in early-career practice.Conclusion: The findings demonstrate that early-career psychologists face significant burnout risks shaped by organizational and systemic stressors, but also employ diverse coping mechanisms and resilience-building strategies. Recovery from burnout is not only possible but often accompanied by professional growth when adequate supports are in place. These results highlight the need for organizational policies, training programs, and supervisory practices that foster resilience, enhance professional identity, and promote sustainable career development for emerging psychologists.